The first documented record of Chvalaea Papp & Földvári, 2002 (Diptera, Hybotidae, Ocydromiinae) from the Australasian Region: a new species and its possible relationship to other members of the genus - Barros, Luana Machado; Soares, Matheus Mickael Mota; de Freitas-Silva, Rafael Augusto Pinheiro; Ale-Rocha, Rosaly (European Journal of Taxonomy, 2022)
Chvalaea australis sp. nov. is described and illustrated, representing the first species of Chvalaea Papp & Földvári, 2002 from the Australasian Region. A discussion of the geographic distribution and the possible relationship among the species of the genus is provided.